As marcas do discurso das mulheres militantes negras: a interseccionalidade de gênero e raça na produção das identidades contemporâneas. - Santos, Kelly Cristine Martins dos (2021)
This thesis, aim promote discourse analysis and the meaning effects of militant black women highlighted in social media, with militancy in the are of blackness. For the choice of these militants, we consider the militancy time, age and different followers among these women, both in Brazil and in the United States of America, in a corpus constituted by the speech of 8 (tem) subjects, who are being highlighted in the last 10 years, reffering areas of education, literature, media and fashion. It is also sought to gather pertinent data to enable us to analyze the discursive marks present by each interviewee, triggering the discursive memory, the interference of the forms of silence, as well as the relationship of the ascension experienced through history and the other elements that will be investigated. To support this work, authors such as Judite Butler, who problematizes the category of women as a concept that encompasses countless heterogeneities, Avtar Brah, who understands the racialization of gender as a contour that still makes “race” an apparently unassailable marker of social difference, as well as Sueli Carneiro, Jurema Werneck as Bell Hooks who help to think concepts of black women and black feminism, among others. Thus, we investigated which subject-position enunciates each militant black woman analyzed, either through the three semi-structured interviews, or through the seven interviews broadcast and collected on websites, on social networks. From the analyzes, there is a comparison of process of identification, counter-identification and desidentification of these analyzed subjects in relation to the Discursive Formation (FD) Precursor of militant black woman. The line of discourse that underlies the study carried out will be the French Discourse Analysis, in the Pecheutian approach in dialogue with the Social Sciences, to demonstrate the importance of intersecionality in the áreas: gender, race and culture. The research points out that, of the analyzed subjects, militant black women, analyzed in this thesis, all show themselves identified to the knowledge registered to the militant black FD addressing the founding discourse and others that permeate this FD.